Odontogenic Facial Cellulitis - Yordany Boza Mejias; Clotilde Mora Pérez; Julio Romero Rodríguez; Surelys Sosa Suárez; Madialys Payo Monzón; Arelys Díaz Duménico (Medisur)
Background: odontogenic facial cellulitis is an acute inflammatory process manifested in very different ways, with a variable scale in clinical presentation ranging from harmless well defined processes, to diffuse and progressive that may develop complications leading the patient to a critical condition, even risking their lives. Objective: To characterize the behavior of odontogenic facial cellulitis. Methods: A descriptive case series study was conducted at the dental clinic of Aguada de Pasajeros, Cienfuegos, from September 2010 to March 2011. It included 56 patients who met the inclusion criteria. Variables analyzed included: sex, age, teeth and regions affected, causes of cellulite and prescribed treatment. Results: no sex predilection was observed, lower molars and submandibular anatomical region were the most affected (50% and 30 4% respectively) being tooth decay the main cause for this condition (51, 7%). The opening access was not performed to all the patients in the emergency service. The causal tooth extraction was not commonly done early, according to the prescribed antibiotic group. Thermotherapy with warm fomentation and saline mouthwash was the most prescribed and the most widely used group of antibiotics was the penicillin. Conclusions: dental caries were the major cause of odontogenic cellulite. There are still difficulties with the implementation of opening access.